2003
DOI: 10.1128/jb.185.16.4672-4682.2003
|View full text |Cite
|
Sign up to set email alerts
|

Mutation in the relA Gene of Vibrio cholerae Affects In Vitro and In Vivo Expression of Virulence Factors

Abstract: The relA gene product determines the level of (p)ppGpp, the effector nucleotides of the bacterial stringent response that are also involved in the regulation of other functions, like antibiotic production and quorum sensing. In order to explore the possible involvement of relA in the regulation of virulence of Vibrio cholerae, a relA homolog from the organism (relA VCH ) was cloned and sequenced. The relA VCH gene encodes a 738-aminoacid protein having functions similar to those of other gram-negative bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
95
2
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(102 citation statements)
references
References 52 publications
2
95
2
3
Order By: Relevance
“…In this study, we have confirmed the role of FTN_1518 in F. novicida U112 as a (p)ppGpp synthetase, and demonstrated that disruption of this gene results in abolition of ppGpp production under conditions of amino acid starvation. This is similar to the situation in Pseudomonas aeruginosa (Erickson et al, 2004) and V. cholerae (Haralalka et al, 2003), in which mutation of the relA gene alone results in reduced (p)ppGpp accumulation. Unlike other organisms such as E. coli, in which both relA and spoT genes need to be inactivated (Xiao et al, 1991), RelA alone appears to be required for (p)ppGpp synthesis in F. novicida during amino acid starvation.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…In this study, we have confirmed the role of FTN_1518 in F. novicida U112 as a (p)ppGpp synthetase, and demonstrated that disruption of this gene results in abolition of ppGpp production under conditions of amino acid starvation. This is similar to the situation in Pseudomonas aeruginosa (Erickson et al, 2004) and V. cholerae (Haralalka et al, 2003), in which mutation of the relA gene alone results in reduced (p)ppGpp accumulation. Unlike other organisms such as E. coli, in which both relA and spoT genes need to be inactivated (Xiao et al, 1991), RelA alone appears to be required for (p)ppGpp synthesis in F. novicida during amino acid starvation.…”
Section: Discussionsupporting
confidence: 62%
“…For example, in Legionella pneumophila, (p)ppGpp triggers a switch between the avirulent replicative phase and the virulent motile phase (Hammer & Swanson, 1999), while in M. tuberculosis, (p)ppGpp accumulation is important for the transition into latency (Ojha et al, 2000;Primm et al, 2000). In addition, the expression of specific virulence genes has been shown to be modified by RelA: in Vibrio cholerae, inactivation of RelA results in decreased expression of cholera toxin and the toxin-coregulated pilus (Haralalka et al, 2003), and a Salmonella enterica spoT/relA mutant has reduced expression of HilA, the central regulator of the Salmonella pathogenicity island (SPI) 1 and SPI 2 virulence genes (Pizarro-Cerda & Tedin, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…QS has been implicated in the regulation of virulence gene expression for a number of pathogenic bacteria. 24,28,30,[41][42][43][44][45][46][47][48] To identify genes regulated by the luxS/AI-2 QS system and CO 2 /bicarbonate, total RNA was isolated from B. anthracis strains 34F 2 and 34F 2 ∆luxS grown in BHI in the presence of 0.8% sodium bicarbonate. CO 2 /bicarbonate is critical for activation of toxin gene expression in B. anthracis.…”
mentioning
confidence: 99%
“…Previous studies demonstrated that the ability of bacteria to synthesize (p)ppGpp and mount a stringent response is an essential physiological adaptation required for stages of pathogenesis, such as initial growth of adherent bacteria [38], toxin production [39], motility [40] and expression of other virulence regulators [41]. Comparative analysis revealed that the IPAV spoT gene (LIF_A2491) has two missense mutations at the amino-acid residues, Val293 and Lys407, resulting in replacement by Ala and Glu, respectively.…”
Section: Mutations Affecting Genes Related To Stress Responsementioning
confidence: 99%